The Healthy Heart-Mind trial: Melatonin for prevention of delirium following cardiac surgery: Study protocol for a randomized controlled trial - Ford, A.; Flicker, L.; Passage, J.; Wibrow, B.; Anstey, Matthew; Edwards, M.; Almeida, O. (2016)
© 2016 Ford et al. Background: Delirium is a common occurrence in patients undergoing major cardiac surgery and is associated with a number of adverse consequences for the individual, their family and the health system. Current approaches to the prevention of delirium include identifying those at risk together with various non-pharmacological and pharmacological strategies, although the efficacy of these is often modest. Emerging evidence suggests that melatonin may be biologically implicated in the development of delirium and that melatonin supplementation may be beneficial in reducing the incidence of delirium in medical and surgical patients. We designed this trial to determine whether melatonin reduces the incidence of delirium following cardiac surgery compared with placebo. Methods/Design: The Healthy Heart-Mind trial is a randomized, double-blind, placebo-controlled clinical trial of 3mg melatonin or matching placebo administered on seven consecutive days for the prevention of delirium following cardiac surgery. We will recruit 210 adult participants, aged 50 and older, undergoing elective or semi-elective cardiac surgery with the primary outcome of interest for this study being the difference in the incidence of delirium between the groups within 7days of surgery. Secondary outcomes of interest include the difference between groups in the severity and duration of delirious episodes, hospital length of stay and referrals to mental health services during admission. In addition, we will assess differences in depressive and anxiety symptoms, as well as cognitive performance, at discharge and 3months after surgery. Discussion: The results of this trial will clarify whether melatonin reduces the incidence of delirium following cardiac surgery.